Identity-Consistent Self-Image Maintenance Following Leader Abuse: Integrating Self-Presentation and Self-Concept Orientation Perspectives - Huang, Lei; Paterson, Ted A.; Wang, Siting (Journal of Management, 2024)
Although coping with an abusive boss can be psychologically demanding, those who suffer from leader abuse often stay in these unpleasant relationships, actively managing the way they are viewed in the eyes of their abusive leader (source of the abuse) and coworkers (observers of the abuse). Accordingly, the abusive supervision literature has relied almost exclusively on an emotional appraisal perspective to study the self-image implications following leader abuse. The present study seeks to add to this emerging line of scholarly conversations by presenting a novel theoretical alternative. Specifically, we integrate self-presentation and self-concept orientation perspectives to portray individuals’ identity-driven self-image maintenance following leader abuse. We argue that only those with a stronger relational self-concept are likely to be motivated to preserve their identity-consistent self-image and present themselves in positive and socially desirable ways toward both their coworkers and leader, following leader abuse. Using survey data collected from working professionals in China across two field studies, we found support for our hypotheses that when employees with a stronger relational self-concept experienced abusive supervision, they were motivated to help their coworkers as a result of their relational reputation maintenance concerns, and to use ingratiation tactics toward their leader due to their image preservation motives. We also offer insights about both the theoretical and practical implications of our research and discuss study limitations and directions for future research.